The meaning of the signifier. On languages, mind and consciousness - Mendívil-Giró, José Luis (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
Jackendoff’s hypothesis on the unconsciousness of meaning implies that the relation between meaning and signifier does not only serve language use for communication, but it plays a central role in the explanation of how language supports consciousness and rational thought. This contribution discusses this hypothesis within generative grammar and considers its implications for the controversy on the relation between language and thought, and for the hypothesis of linguistic relativity.